Bioactive oligomers from natural polyhydroxyalkanoates and their synthetic analogues - Adamus, G.; Kurcok, P.; Radecka, I.; Kowalczuk, M. (Polimery, 2021)
Contemporary reports on the bioactive oligomers derived from natural aliphatic co-polyesters (PHA) and their synthetic analogues, formed through anionic ring-opening polymerization (ROP) of β-substituted β-lactones are presented. Synthetic routes for such oligomers, developed mostly by Polish authors, are discussed. The described approaches enable design of novel biodegradable and bioactive oligomers for diverse applications in medicine, cosmetic industry and agrochemistry.